Penerapan Clean Arsitektur Menggunakan Mobile Platform Berbasis Flutter Untuk Aplikasi Layanan Kapal - Putri, Amanda; Asri, Jefry Sunupurwa; Anwar, Nizirwan; Widiantono, Adi (Fakultas Teknik Universitas Persada Indonesia YAI, 2025)
Indonesia's mobile technology adoption rate of 77.02% provides a great opportunity forcompanies to improve their services through mobile platforms. PT ABC, a ship service providerfor various needs, currently only uses web-based applications and needs a mobile-based shipservice application to increase efficiency and flexibility. This research aims to implement CleanArchitecture on a Flutter-based mobile platform to improve the structure and facilitate codemaintenance in ship service applications. The research method used is the prototyping method,with stages including Communication, Quick Plan, Modelling Quick Design, Prototype Formationand Deployment Delivery & Feedback. This approach enables faster application development,earlier identification of potential changes, and reduced risk of failure or mismatch with user needs.The results showed that the application of Clean Architecture in mobile-based ship service applications was successfully implemented so that it provided ease of maintenance. Blackboxtesting with 10 test cases ensures that the application functions as expected and is ready to be usedby PT ABC. User Acceptance Testing also shows that this application meets the needs of users andincreases the company's responsiveness to market changes, the test results reached 86.83%. Withthe division of business logic into usecases folders, the overall efficiency of development, flexibilityof change, and ease of maintenance of the system is increased. In conclusion, Clean Architectureproved to be the right solution to optimise PT ABC's business operations, facilitate applicationmaintenance and testing, and improve code understanding and readability for developers